MEN AND WOMEN DIFFERENCES IN USING LANGUAGE: A CASE STUDY OF STUDENTS AT STAIN KUDUS - Sri Wahyuningsih (EduLite: Journal of English Education, Literature and Culture, 2018)
This paper mainly investigates the differences between men and women in using language especially the students’ conversation at STAIN Kudus. These differences were viewed from the aspects of vocabulary, attitudes, syntax and non-verbal differences. This research belongs to a qualitative research. Data were collected through transcripts of a video documentation played by the students of Sharia Department at STAIN Kudus. The findings showed that male and female students have shown differences in their form, content, and use. Men tend to be more directive. Besides, they used more simple words. On the other hand, women were more expressive and polite in using language. In addition, they used more gestures and words signifying feeling, emotional and psychological state.